Crise economique et changements politiques en Indonesie: premiers effets sur le secteur forestier - Sunderlin, William D. (1999)
Indonesia's economy receded in 1998, and the national currency has lost more than 70% of its value. Expansion of agriculture is one of the main ways to overcome the crisis: 1) relatively independent of the dollar economy; 2) provision of basic needs commodities; 3) reduction of unemployment; 4) reduction of costly food imports; 5) Indonesian commodities cheaper in the export market - costs in rupiahs, earnings in US$. Another means is access to loans from IMF. The author reviews the likely effects on the forest sector. (1) Decreased demand for Indonesian plywood from main importers (Japan, South Korea and Taiwan) is largely compensated by increased demand from other countries and Malaysia's decision to restrict its wood product exports. (2) Expansion of agriculture will occur partly at the expense of forest cover: spontaneous clearing by farmers, and large scale clearings for agro-industry plantations, mainly oil palm, then cocoa, coffee, rubber trees, pepper, as well as shrimp ponds in mangroves. (3) Transmigration will probably not slow down, foreign aid compensating for the decline of State aid. (4) Unemployed people in the urban sector migrate to rural areas, and young people in the rural areas remain there which may increase pressure on forests for three reasons: a) incentives to expand plantations for export; b) incentives to produce food crops locally (rice, maize, soya) to reduce imports; c) shortage of capital for inputs, that may encourage extensive agriculture. (5) Expansion of mining in forest areas (coal, iron, and nickel) may lead to degradation of important protection forests. (6) The likely slowdown of major road programmes will reduce their direct and indirect impacts on forests. (7) Policy changes as a prerequisite to IMF loans will have negative effects on forest conservation when they encourage plantations for export (oil palms). (8) President Habibie has launched a wave of policy reforms to remedy former abuses in granting timber concessions, and the resulting forest deterioration. In addition, new laws should promote community-based forest management. In conclusion, the economic crisis appears a threat to Indonesia's forests, in view of the trend to increase foreign exchange earnings through the export of forest and agricultural products.